Pedagogical Preconditions for the Development of Productive Communication Skills within the Special Course “Computers and Banking”; Advances in Intelligent Systems and Computing; Vol. 907 : Going Global through Social Sciences and Humanities: A Systems and ICT Perspective (GGSSH) - Nizkodubov G. A. Gavriel Anatolevich; Kuklina S. S. Svetlana; Obskov A. V. Aleksandr Vladimirovich; Vikulina M. A. Maria; Kachalov N. A. Nikolay Aleksandrovich (Advances in Intelligent Systems and Computing book series, 2019)
Title screen